On the benefits of formalization: Panel evidence from Vietnam - Amadou Boly (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper examines the relationship between formalization and firm-level outcomes in Vietnam using a unique panel dataset. Results show that switching firms differ from informal nonswitching firms, confirming heterogeneity. We also find that becoming formal leads to increased profits, value added, and revenue. The performance of switching firms is higher than that of informal ones, but remains lower compared to non-switching formal firms. Our results suggest that the benefits of formalization materialize in the short term and persist over time. These benefits run through access to improved equipment, larger customer base, advertising, and business association membership, but not access to credit.
Keywords: D21; O12; O17; 330; benefits of formalization; informal sector